2018
DOI: 10.21608/ejbo.2018.1820.1126
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Bioethanol Productivity from Sugarcane Molasses by Saccharomyces cerevisiae Y17 KP096551

Abstract: is capable of producing approximately 106kg of sugar and 46kg of molasses. A typical molasses to ethanol conversion rate is 4kg of molasses/L ethanol (Lavarack, 2001). However, this rate can vary based on production practices and sugar content of the molasses (Nguyen et al., 2009 andSilalertruksa &Gheewala, 2010).Molasses composition is usually influenced by the variety and maturity of the cane and beet, soil, climate and the processing conditions in the factory (El-Gendy et al., 2013). High yielding and effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Additionally, industrial sugar production from beets and sugarcane generates molasses, an opaque, nutrient-rich liquid, as a byproduct, thus providing a renewable, reliable, readily available, and low-cost raw material that can be used to feed most microorganisms, as it contains carbon, nitrogen, phosphorus, sodium, potassium, and magnesium. A concentrated sugar substrate such as molasses can be used to obtain a high yield of bio-based products via industrial-scale fermentation 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, industrial sugar production from beets and sugarcane generates molasses, an opaque, nutrient-rich liquid, as a byproduct, thus providing a renewable, reliable, readily available, and low-cost raw material that can be used to feed most microorganisms, as it contains carbon, nitrogen, phosphorus, sodium, potassium, and magnesium. A concentrated sugar substrate such as molasses can be used to obtain a high yield of bio-based products via industrial-scale fermentation 6 .…”
Section: Introductionmentioning
confidence: 99%
“…nitrogen, phosphorus, sodium, potassium, and magnesium. A concentrated sugar substrate such as molasses can be used to obtain a high yield of bio-based products via industrial-scale fermentation 6 .…”
mentioning
confidence: 99%
“…1). Several investigators reported that, crops contain free sugars make them more cost-effective feedstocks in bioethanol industry (Ensinas et al, 2009;Dhaliwal et al, 2011;Rasmey et al, 2018). Furthermore, the cellulose content recorded in T. nilotica (25.02%) was greater twofold than that of P. dioscoridis (10.04%) ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…According to [26], steam explosion and liquid hot water pretreatments of fruit peels can generate soluble inhibitors which hamper the cellulase enzymatic activity and hence the released reducing sugars. Toxic and inhibitory compounds vary with the pretreatment method and the waste type that might include soluble sugars, organic acids (levulinic, acetic and formic acid), and furan derivatives (hydroxymethyl fulfural) [9,27].…”
Section: Effect Of the Simultaneous Saccharification And Fermentationmentioning
confidence: 99%